Electrocution risk for the endangered Crowned Solitary Eagle and other birds in semiarid landscapes of central Argentina - Galmes, Maximiliano Adrian (2017)
High mortality by electrocution has been suggested to be the main factor behind the reduction of several birds of prey populations across the world. Almost nothing is known, however, about the impact of power lines on this group of birds in the Neotropical Region. Here we estimate electrocution rates for birds on power lines covering both arid and semiarid biomes of central Argentina. We conducted six bi-monthly power line and raptor surveys throughout 355 km of lines and roads covering an area of approximately 12,000 km2. We described the structural design of 3,118 surveyed electricity pylons. We found 34 electrocuted individuals of four bird families that constitute an annual bird electrocution rate of 0.011 bird/pylon/year. Bird electrocution occurred mostly on concrete pylons with jumpers above the cross-arm. Larger birds of prey had a higher electrocution rate than smaller species. The Crowned Solitary Eagle Buteogallus coronatus was disproportionately affected by this mortality source when compared with its low population density. Electrocution incidents occurred mostly in a few electric pylon designs that represent only 10.2 % of the power pylons monitored in the study area. Therefore, the change or modification of a small fraction of pylons would almost eliminate bird electrocution incidents in our study area. Our results prove that electrocution is a relevant cause of mortality for Crowned Solitary Eagles and urgent mitigating actions are needed to reduce this mortality factor.